PENCIPTAAN MATA PENCAHARIAN ALTERNATIF: STRATEGI PENGURANGAN KEMISKINAN DAN PERLINDUNGAN SUMBER DAYA LAUT (STUDI KASUS KOTA BATAM DAN KABUPATEN PANGKAJENE DAN KEPULAUAN) - Mita Noveria; Meirina Ayumi Malamassam (Jurnal Kependudukan Indonesia, 2015)
One attempt to alleviate poverty of fishermen is, among others, by creating alternative income generating activities to facilitate additional income. The activities are implemented through diversification of household income’s sources. This enables fishermen to carry out jobs other than fisheries. For coastal and small island inhabitants, this situation also serves as an effective effort to conserve marine resources. The reason is because alternative income generating activities could reduce the high dependency of fishery households on marine resources. This paper aims to assess alternative income-generating activities implemented through the Coral Reef Rehabilitation and Management Program (COREMAP). It is based on two COREMAP study sites, ie. the City of Batam in the Province of Riau Islands and the district of Pangkajene Islands (Pangkep) in the Province of South Sulawesi. The study applied quantitative method (survey) and qualitative method (in-depth interview, FGD, and observation) to collect the data. However, this paper only analyzed the qualitative data, particularly on the supporting and challenges factors in implementing income-generating activities. The result of data analysis shows that the alternative income generated activities offered by the program tend to neglect the work habits of the targeted groups. For example, the activities requested target population to work collectively in a group. However, in reality, they are not accustomed to such manner. Moreover, the initiated income generated activities took quite long time to harvest, while the target population normally carried out quick yielding jobs.